Drug-Eluting Stents Versus Bare Metal Stents for Percutaneous Coronary Intervention in Kidney Transplant Recipients. Issue 4 (April 2017) - Lenihan, Colin R.; Montez-Rath, Maria E.; Winkelmayer, Wolfgang C.; Chang, Tara I.
Abstract : Background: The comparative effectiveness of percutaneous coronary intervention (PCI) with drug-eluting stents (DES) versus bare metal stents (BMS) has not been studied in the kidney transplant population. Methods: Using the US Renal Data System, we identified 3245 kidney transplant patients who underwent PCI between April 2003 and December 2010; 2400 and 845 patients received DES and BMS, respectively. We used propensity score matching and inverse probability of treatment weighting to create DES- and BMS-treated groups whose observed baseline characteristics were well-balanced. The associations between stent type and the outcomes of (1) death; (2) death or myocardial infarction (MI); (3) death, MI, or repeat revascularization (RR); and (4) hospitalized bleeding were compared using Cox proportional hazards regression. Results: Drug-eluting stent use increased during the study period, mirroring the trend described in the general population. In the propensity score-matched cohort, no significant association among DES (vs BMS) use and outcomes was observed at 1 and 2 years of follow-up. However, at 3 years, DES was associated with 20% (95% confidence interval [CI], 4-33%) lower risk of death, 15% (95% CI, 1-27%) lower risk of death or MI, and 14% (95% CI, 2-24%) lower risk of death, MI, or repeat revascularization. There were no significant differences in rates of hospitalized bleeding at any time point. Results were similar in the inverse probability of treatment weighting analysis. Conclusions: In this retrospective study of US kidney transplant recipients undergoing PCI, DES was associated with better clinical outcomes beyond 2 years of follow-up. Abstract : This retrospective registry study of US kidney transplant recipients undergoing percutaneous coronary intervention suggests that the use of drug-eluting stents is increasing and is associated lower risk of death, myocardial infarction or repeat revascularization compared to bare-metal stents. Supplemental digital content is available in the text.